Two-year free of complications during antiviral therapy predicts stable re-compensation in immediate-treatment HBV-related decompensated cirrhosis. (3rd April 2023) - He, Zhiying; Zhou, Jialing; Tian, Yu; Wu, Shanshan; Sun, Yameng; Ou, Xiaojuan; Jia, Jidong; Wang, Bingqiong; Wu, Xiaoning; You, Hong
Abstract: Background and aims: Disease progression could be altered or even reversed in decompensated patients with HBV-related cirrhosis once they initiate antiviral therapy. However, little is known about the stable re-compensation in these patients. Methods: In this retrospective study, HBV-related liver cirrhosis patients were consecutively enrolled at the first decompensated event of ascites or variceal hemorrhage (VH), and divided into immediate-treatment, on-treatment and delayed/no treatment groups. Patients were followed up to at least presence of second decompensation event or to June 2021. Re-compensation was defined as patients who did not occur second (further) decompensation during follow-up. Results: A total of 130 HBV-related decompensated cirrhotic patients were included with a median follow-up of 61.0 (41.6, 72.0) months. The cumulative incidence of re-compensation at year 6 was 39.0, 9.8 and 6.6 in immediate-treatment, on-treatment and delayed/no treatment group ( p  = 0.001). Among 87 patients in immediate-treatment group, thirty-seven (37/87, 42.5%) were recognized as stable re-compensation. Seventy percent (35/50) of second decompensated events occurred in the first 2 years. In patients free of 2-year decompensated complications, about 71.2% (37/52) maintained stable re-compensation. The cumulative incidence of death (and/or transplantation) and HCC in patients free of 2-year decompensated complications or not was 2.9 vs. 27.3% (HR 9.4, 95% CI 2.2–40.0, p  = 0.002) and 12.6 vs. 37.7% (HR 4.5, 95% CI 1.5–13.3, p  = 0.006), respectively. Conclusions: In decompensated patients with HBV-related cirrhosis, about 40% in immediate-treatment group maintained stable re-compensation during 6 years of antiviral therapy. Two-year free of complications could predict stable re-compensation.